INDUSTRIES AND THE ROLE OF DIGITAL MEDIUM - Adinugroho, Indro (Jurnal InterAct, 2017)
Rapid growth in information technology forces various industries and business owners to think strategically to reach public attention. This condition also brings the logical consequence of using online medium as their primary marketing tools. Various online medium or usually called as social media such as Twitter, Path, Facebook and Instagram have been used by numerous industries as tools to communicate their ideas, brands and promotion into public. Along with this condition, industries need to think strategically to develop contemporary marketing communication strategy. This is a case study focusing on two brands in Indonesia, Pocari Sweat and Telkom. Result shows these two brands using different approach in twitter as their marketing tool. Pocari sweat focused on brand awareness, whereas Telkom focused on corporate identity as Indonesian company. Despite differences in marketing strategy, there is no significant difference in the degree of valence and arousal from tweets which discussed Pocari Sweat and Telkom.